Reply to Mikolajczak et al - Matuschewski, Kai; Borrmann, Steffen (The journal of infectious diseases, 2010)
The correspondence from Mikolajczak et al [Mikolajczak SA, Vaughan AM, Soliman JMB, Kappe SHI. A genetically attenuated parasite vaccine does not require liver stage persistence to elicit sterile protective immunity against sporozoite-induced malaria in mice. J Infect Dis 2010; 201:1270-1271] gives us an opportunity to refine the principles of 2 distinct whole-organism antimalaria vaccine concepts.
Gesehen am 30.05.2023